2020
DOI: 10.3390/healthcare8030338
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rate and Predictors of Mortality in Hospitalized COVID-19 Patients with Diabetes

Abstract: Studies have confirmed COVID-19 patients with diabetes are at higher risk of mortality than their non-diabetic counterparts. However, data-driven evidence of factors associated with increased mortality risk among hospitalized COVID-19 patients with diabetes is scarce in South Korea. This study was conducted to determine the mortality rate and identify risk factors of mortality among hospitalized COVID-19 patients with type 2 diabetes in Gyeongsangbuk-do province, South Korea. In this hospital-based, cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 29 publications
(40 reference statements)
4
36
5
1
Order By: Relevance
“…Previous data from two Korean dedicated centers for COVID-19 revealed 17.9% lymphopenia in a total of 352 patients: The proportion of lymphopenia among the patients is comparable to that of our cohort. As far as we know, there have been four cohort studies that explored both the mortality rate of COVID-19 of entire subject in their cohort and a proportion of lymphopenia, as defined by ALC < 1000/mm 3 , identical to that in our study ( Table S2 ) [ 17 , 25 , 27 , 28 ] Interestingly, the order of mortality for each evaluation was consistent with that of a proportion of lymphopenia. These results could illustrate that mild lymphopenia, defined as ALC < 1000/mm 3 , could be a feasible biomarker to predict mortality of COVID-19.…”
Section: Discussionsupporting
confidence: 54%
“…Previous data from two Korean dedicated centers for COVID-19 revealed 17.9% lymphopenia in a total of 352 patients: The proportion of lymphopenia among the patients is comparable to that of our cohort. As far as we know, there have been four cohort studies that explored both the mortality rate of COVID-19 of entire subject in their cohort and a proportion of lymphopenia, as defined by ALC < 1000/mm 3 , identical to that in our study ( Table S2 ) [ 17 , 25 , 27 , 28 ] Interestingly, the order of mortality for each evaluation was consistent with that of a proportion of lymphopenia. These results could illustrate that mild lymphopenia, defined as ALC < 1000/mm 3 , could be a feasible biomarker to predict mortality of COVID-19.…”
Section: Discussionsupporting
confidence: 54%
“…Fourteen studies reported the outcome of mortality, and seven studies reported the outcome of length of hospital stay. Of the 19 studies, 10 studies were performed in China [ 18 , 20 22 , 24 , 26 31 ], two in USA [ 17 , 23 ], two in France [ 13 , 14 ], two in Korea [ 12 , 19 ], one in each of the following countries: UK [ 16 ], Qatar [ 25 ], and South Korea [ 15 ]. Detailed characteristics of the patients included in the meta-analysis are presented in Supplementary Digital File.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies reported in-hospital mortality [ 12 , 13 , 15 19 , 21 , 22 , 24 , 25 , 28 30 ]. The mortality of DM vs non-DM patients was 21.3 versus 6.1%, respectively (OR = 2.39; 95%CI: 1.65, 3.46; I 2 = 62%; P < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study on Chinese patients reported that 14% of the COVID-19 patients who survived had diabetes as associated comorbidity, however 31% of those did not survive [ 21 ]. Likewise, the mortality rate was much higher among Korean COVID-19 patients with diabetes compared to those without (20.0% vs. 4.8%) [ 25 ]. Therefore, like other countries, Bangladeshi diabetic patients are more likely to have worse complications if they get infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%